Suppression of electromagnetic interference using screening and shielding techniques within switching cells - Zhang, Zhe; Johnson, Christopher Mark (2017)
in this paper we introduce the use of combination of screening and shielding to suppress electromagnetic interference (EMI) generated by a switching cell. We investigate the screening of common mode (CM) currents and the shielding of magnetic fields generated by a model switching cell using a combination of simulation tools and measurements. Simulation results align with measurements very well up to 100MHz, confirming that a relatively simple model can be used to investigate different arrangements of screen layer. We demonstrate that electromagnetically coupled currents produced by rapidly changing voltages and currents in the main switching circuit can be circulated back to the local DC-link or absorbed rather than being coupled to the external environment.